2017
DOI: 10.15406/bij.2017.01.00013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microbial Contamination in Frequently Used Fomites in Kuwait

Abstract: The occurrence of potential pathogens and the levels of contamination at individual sites, particularly in fitness club, gas station, home, hospital, and supermarket in Kuwait is described in this paper. The samples were collected using sterile swab sticks. Results obtained showed the highest bacterial count of 2.8 log10 CFU/ml in bathroom doorknobs at gas station, while the least was obtained from pantry in hospital with 1.3 log10 CFU/ml. Prevalent isolated bacterial contaminants were Staphylococcus epidermid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
0
1
1
Order By: Relevance
“…Though this figure is not significantly high, more number of GNB was isolated. This is not in agreement with other studies where Gram-positive organisms (80%) were abundant rather than Gram-negative organisms (20%) [8, 9].…”
Section: Discussioncontrasting
confidence: 89%
“…Though this figure is not significantly high, more number of GNB was isolated. This is not in agreement with other studies where Gram-positive organisms (80%) were abundant rather than Gram-negative organisms (20%) [8, 9].…”
Section: Discussioncontrasting
confidence: 89%
“…Most of the isolates were Gram-positive bacteria, which is in accordance with the studies by Al-Harbi et al and Al-Harmoosh et al who isolated similar groups of bacteria from door handles [12,13]. Previous studies have shown that Bacillus sp.…”
Section: Discussionsupporting
confidence: 89%
“…Pese a que la presencia bacteriana en diversos fómites ha sido descrita con un predominio principalmente por bacterias grampositivas, como Bacillus sp., y S. aureus 10,11 , en este trabajo se encontró un predominio de bacterias gramnegativas con un 76,67% dado principalmente por A. baumannii frente a un 23,33% de grampositivas; este fenómeno puede explicarse de acuerdo a lo reportado por Angelakis, et al, 2014 12 , quienes indican que este grupo de patógenos gramnegativos tienen mayor capacidad de supervivencia en superficies inertes, trayendo como consecuencia una alta diseminación; en especial si se tiene en cuenta su capacidad de formación de biopelículas y transmisión de información genética por medio de plásmidos con genes de resistencia asociados a betalactamasas 13 ; demostrando a su vez, que los elementos inanimados se comportan como un factor determinante en la diseminación de bacterias con resistencia en la comunidad. Adicionalmente cabe recordar que: Acinetobacter sp., E. faecalis, K. pneumoniae y P. aeruginosa, hacen parte de la lista de prioridad de la OMS, en donde se consideran como patógenos de difícil manejo, por lo que encontrarlos en circulación en elementos de alta circulación en la comunidad debería ser considerado por las autoridades de salud pública de cada región 14 .…”
Section: Discussionunclassified